The Relationship Between Family Support and Self-Care in Heart Failure Patients: A Cross-sectional Study in Garut City, Indonesia - Sulastini, Sulastini; Aditya Nugraha, Bambang; Nurul Madinah, Rahmi (Journal of Health and Nutrition Research, 2025)
Heart failure is a pathophysiological condition due to impaired heart function in pumping blood that is chronic and progressive, and contributes to high morbidity and mortality rates. Reducing these rates requires a treatment strategy that maintains the health and well-being of patients, one of which is through effective self-care management. In its implementation, the role of family is an important aspect as a source of non-medical support that can motivate patients to undergo treatment. This study aimed to analyze the relationship between family support and self-care practices among individuals with heart failure attending polyclinics in Garut City. A quantitative cross-sectional design was employed, involving 105 participants who were selected through purposive sampling. Data were collected using a family support questionnaire the Caregiver Contribution to Self-Care of Heart Failure Index version 2 (CC-SCHFI v.2), then The Spearman rank correlation test was used for data analysis. The results showed that most participants had high levels of family support (81%), and demonstrated moderate self-care practice (88,6%).  There was a strong and significant positive correlation between family support and self-care behavior (r = 0.680; p < 0.001), suggesting that better family support is associated with improved self-care practices among heart failure patients. Family support significantly enhances self-care behavior in heart failure patients. Involving family members in disease management programs is essential to promote better health outcomes.